Wdrażanie controllingowej koncepcji zarządzania w przedsiębiorstwie państwowym - doświadczenia praktyczne - Węgrzyn, Adam (Implementing the Controlling - Based Management in a State - Owned Enterprise - Practical Experience, 2007)
This article presents the author's practical experience in the process of controlling implementation in a state-owned enterprise OGP Gaz-System S.A. In the author's opinion in the process of controlling implementation the initiative and the main responsibilities do not always rest with the Company's Management Board and Headquarters. In the case in question the initiators and sponsors of changes were a group of branch directors who on their own premises initiated the creation of costs responsibility centers, the preparation and implementation of a proprietary budgeting methodology, development and deployment of software supporting costs budgeting and budget monitoring. According to the author, in order to guarantee efficiency the process of controlling implementation must be adapted to the specific and changing conditions existing in a company. In the presented example the first phase of this conception implementation focused on structural and cultural changes. Structural changes consisted in modernization of a traditional organizational structure towards a structure based on responsibility centres - in conjunction with delegating powers and responsibilities to lower management levels. Whereas cultural changes aimed at increasing: employees' participation in the decision-making processes, employees' co-responsibility for planning and realization of costs budgets and at improving the thrift and so called cost awareness. Another stage of controlling implementation was connected with informatization. In the author's opinion an enterprise of strategic significance for the country's economy, such as OGP Gaz-System S.A., should have a professional ERP class IT system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 507-516